The Ageing Process Affects the Antioxidant Defences and the Poly (ADPribosyl)ation Activity in Cistus Incanus L. Leaves - Carmen Arena; Luca Vitale; Anna Rita Bianchi; Carmela Mistretta; Ermenegilda Vitale; Costantino Parisi; Giulia Guerriero; Vincenzo Magliulo; Anna De Maio (MDPI AG, 2019)
The ageing process in living organisms is characterised by the accumulation of several deleterious changes occurring in cells and tissues. The increase of reactive oxygen species with the advancement of age is responsible for the oxidative damage to proteins, lipids and DNA, enhancing the risk of diseases. The antioxidant response and the activation of the poly(ADP-ribosyl)ation process represent the first defences activated by organisms at all life stages to counteract damage to cell structures and genomic material. The regulation of poly(ADP ribosyl)ation with age is little known in plants, especially in combination with antioxidant defences modulation. In this study, the relationships between poly (ADP-ribose) polymerase (PARP) activity and enzymatic and non-enzymatic antioxidant pool have been studied together with the photosynthetic apparatus efficiency in the Mediterranean species Cistus incanus L., examining leaves at different developmental stages: young, mature and senescent. The photosynthetic performance was evaluated by chlorophyll a fluorescence measurement, the total soluble and fat-soluble antioxidant capacity, as well as the activities of enzymes superoxide dismutase (SOD), catalase (CAT), peroxidase (POD) and glutathione-S-transferase (GST), were determined by spectrophotometer, PARP activity was assessed by radioactive labelling. The highest photochemical activity was observed in young leaves, together with the highest GST activity. With the progress of the ageing process, the non-enzymatic antioxidant pool (namely ascorbic acid, α-tocopherol) declined, reaching the lowest value in senescent leaves, whereas PARP activity rose significantly. The overall results indicate that the decline of photosynthetic apparatus efficiency during senescence is due to the reduction of specific defences against oxidative damages, which increase the damages to DNA, as demonstrated by PARP activity rise.